KEBERLANJUTAN SISTEM AGRIBISNIS PADI SAWAH (STUDI KASUS DI KABUPATEN KUBU RAYA) (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
Kubu Raya Regency is one of the main rice production centers in West Kalimantan, but rice production and productivity in the last several years were stagnant because of various complex and multi-dimension factors. The objective of this research was not only to analyze sustainability status and index but also factors affected sustainability of rice agribusiness system. Method used in this research was survey method and in-depth interview using Rap-Paddy/multi dimensional scaling (MDS) tool analysis. Analysis result of Rap-Paddy ordination using MDS method show that multi-dimensionally of sustainability index of rice agribusiness system was 47.05. It categorized as less sustainable. Index of sustainability status for each dimension were as follows: ecology was 48.77 % (less sustainable), economy was 49.33 % (less sustainable), socio-culture was 50.02 % (sustainable enough), institutions was 43,24 % (less sustainable), and technology was 46,70 % (less sustainable). Based on the leverage analysis result using 95 % of confident interval, it found that among 48 attributes there were 17 attributes that need to be handled because it was sensitive and affected its sustainability status and index of rice agribusiness system in Kubu Raya Regency.Keyword : sustainability, agribusiness, rice, MDS, Rap-Paddy